Potentials of grinding process simulations for the analysis of individual grain engagement and complete grinding processes - Wiederkehr, Petra; Grimmert, Adina; Heining, Ines; Siebrecht, Tobias; Wöste, Florian (Frontiers in Manufacturing Technology, 2023)
Grinding processes are very complex due to the multitude of influencing parameters, resulting from the stochastic tool topography with numerous geometrically undefined abrasive cutting edges. Thus, the efficient design and optimization of these processes is a challenging task. Process simulations can be used as a flexible tool for analyzing interdependencies between several process parameters and identifying suitable process parameter values. For a precise process analysis, the choice of a process model with a corresponding model scale as well as the representation of optimization-relevant process effects are necessary. While macroscopic model approaches can be used to estimate the thermo-mechanical loads occurring in the contact zone, explicit modeling of the individual abrasive grains is required to predict the resulting surface topographies. In this paper, the use of simulation approaches for different scales for the analysis of different process parameters is discussed on the basis of selected application examples. The analysis of surface structuring in NC form grinding processes, e.g., was conducted by using an explicit geometric modeling of the individual abrasive grains in a geometric-physically based simulation approach to estimate wear-dependent resulting surface topographies. The parameterization of the empirical models used was based on numerical approaches for the detailed analysis of individual grain interventions. Using the complex production process of a turbine blade as an example, the utilization of a macroscopic simulation model for estimating the thermo-mechanical loads and the resulting temperatures in the workpiece during profile grinding processes is discussed.